Disruption of O-GlcNAc Cycling in C. elegans Perturbs Nucleotide Sugar Pools and Complex Glycans - Ghosh, Salil K.; Bond, Michelle R.; Love, Dona C.; Ashwell, G. Gilbert; Krause, Michael W.; Hanover, John A. (Frontiers in Endocrinology, 2014)
The carbohydrate modification of serine and threonine residues with O-linked beta-N-acetylglucosamine (O-GlcNAc) is ubiquitous and governs cellular processes ranging from cell signaling to apoptosis. The O-GlcNAc modification along with other carbohydrate modifications, including N-linked and O-linked glycans, glycolipids, and sugar polymers, all require the use of the nucleotide sugar UDP-GlcNAc, the end product of the hexosamine biosynthetic pathway. In this paper, we describe the biochemical consequences resulting from perturbation of the O-GlcNAc pathway in C. elegans lacking O-GlcNAc transferase and O-GlcNAcase activities. In ogt-1 null animals, steady-state levels of UDP-GlcNAc/UDP-GalNAc and UDP-glucose were substantially elevated. Transcripts of genes encoding for key members in the Hexosamine Biosynthetic Pathway (gfat-2, gna-2, C36A4.4) and trehalose metabolism (tre-1, tre-2, and tps-2) were elevated in ogt-1 null animals. While there is no evidence to suggest changes in the profile of N-linked glycans in the ogt-1 and oga-1 mutants, glycans insensitive to PNGase digestion (including O-linked glycans, glycolipids, and glycopolymers) were altered in these strains. Our data supports that changes in O-GlcNAcylation alters nucleotide sugar production, overall glycan composition, and transcription of genes encoding glycan processing enzymes. These data along with our previous findings that disruption in O-GlcNAc cycling alters macronutrient storage underscores the noteworthy influence this posttranslational modification plays in nutrient sensing.